Nonlinear interfacial rheology and atomic force microscopy of air-water interfaces stabilized by whey protein beads and their constituents. (April 2020) - Yang, Jack; Thielen, Ilonka; Berton-Carabin, Claire C.; van der Linden, Erik; Sagis, Leonard M.C.
Abstract: In recent years, food-grade Pickering particles have gained considerable interest, because of their ability to form stable emulsions and foams. Such Pickering stabilizers are often produced by aggregation of proteins, which typically results in a mixture of cross-linked particles and unbound proteins (smaller constituents). This study focuses on the possible contribution to the interfacial behaviour of these smaller constituents in whey protein isolate (WPI) bead suspensions, which are produced by cold-gelation of WPI aggregates. To understand the interfacial properties of the total mixture, we have studied the involved structures and interactions hierarchically, from native WPI, to aggregates, and finally gel beads. Air-water interfaces were subjected to large amplitude oscillatory dilatation (LAOD) and shear (LAOS) using a drop tensiometer and a double wall ring geometry. The non-linear responses were analysed using Lissajous plots. The plots of native WPI- and aggregates-stabilized interfaces showed a rheological behaviour of a viscoelastic solid, while bead-stabilized interfaces tended to have a weaker and more fluid-like behaviour. The interfacial microstructure was analysed by imaging Langmuir-Blodgett films of the protein systems using atomic force microscopy (AFM). The native WPI and aggregate films had a highly heterogeneous structure in which the proteins form a dense clustered network. The beads are randomly distributed throughout the film, separated by large areas, where smaller proteinaceous material is present. This smaller and surface-active material present in the bead suspensions plays an important role in interface stabilization, and could also largely influence the macroscopic properties of interface-dominated systems. Graphical abstract: Image 1 Highlights: Small constituents of WPI beads play a dominant role in interface stabilization. Mixtures of WPI beads and constituents form a weak and mobile air-water interface. Native WPI and aggregates behave as viscoelastic solids at an air-water interface. All proteins exhibit dynamic heterogeneity in their stress-relaxation response. The protein systems form heterogeneous structures at an air-water interface.